Manipulating surface-plasmon-polariton launching with quasi-cylindrical waves - Sun, Chengwei; Chen, Jianjun; Yao, Wenjie; Li, Hongyun; Qihuang Gong (Scientific Reports, 2015)
Launching the free-space light to the surface plasmon polaritons (SPPs) in a broad bandwidth is of importance for the future plasmonic circuits. Based on the interference of the pure SPP component, the bandwidths of the unidirectional SPP launching is difficult to be further broadened. By greatly manipulating the SPP intensities with the quasi-cylindrical waves (Quasi-CWs), an ultra-broadband unidirectional SPP launcher is experimentally realized in a submicron asymmetric slit. In the nanogroove of the asymmetric slit, the excited Quasi-CWs are not totally damped, and they can be scattered into the SPPs along the metal surface. This brings additional interference and thus greatly manipulates the SPP launching. Consequently, a broadband unidirectional SPP launcher is realized in the asymmetric slit. More importantly, it is found that this principle can be extended to the three-dimensional subwavelength plasmonic waveguide, in which the excited Quasi-CWs in the aperture could be effectively converted to the tightly guided SPP mode along the subwavelength plasmonic waveguide. In the large wavelength range from about 600 nm to 1300 nm, the SPP mode mainly propagates to one direction along the plasmonic waveguide, revealing an ultra-broad (about 700 nm) operation bandwidth of the unidirectional SPP launching.